Productive Dynamics of the Automotive Sector and Manufacturing in the Northern Border of Mexico: An Analysis with Panel Data, 1980-2014 - CARBAJAL SUÁREZ, Yolanda; CARRILLO MACARIO, Berenice; DE JESÚS ALMONTE, Leobardo (Frontera Norte, 2018)
It analyzes the link between the manufacturing and automotive sector in the federal entities of the northern border of Mexico (Baja California, Sonora, Chihuahua, Coahuila, Nuevo León and Tamaulipas). It provides empirical evidence that the growth dynamics of the automotive sector in this region has driven the manufacturing growth. A model is estimated with panel data of the production of manufacturing in the entities of the region. The results suggest that the automotive industry, without being the only factor, is driving the growth of manufacturing in the northern region of the country. This creates important benefits in variables, such as IED, employment, production, and manufacturing rating among others.